2023
DOI: 10.3390/foods12040853
|View full text |Cite
|
Sign up to set email alerts
|

Milk from Halari Donkey Breed: Nutritional Analysis, Vitamins, Minerals, and Amino Acids Profiling

Abstract: This current research set out to characterize Halari donkey milk by investigating its nutritional constituents, including its proximate analysis, water activity, titratable acidity, energy, and microbiological analysis. A comprehensive profiling of vitamins, minerals, and amino acids was also carried out. It was found that the composition of Halari donkey milk was consistent with previously published donkey milk literature and was comparable to that of human milk. Halari donkey milk has low 0.86 ± 0.04% fat co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Based on the composition analysis of milk from the Istrian jennies and the Littoral Dinaric jennies, the values of lactose, protein, fat, and ash content fell within the range of the previously determined values [17,18,[20][21][22][23][25][26][27][28][29][38][39][40][41]. These studies reported lactose content ranging from 5.75 to 7.25%, protein content ranging from 1.42 to 2.04, fat content ranging from 0.11 to 1.16%, and ash content ranging from 0.36 to 0.51% (Figure 2).…”
Section: Donkey Milkmentioning
confidence: 82%
See 3 more Smart Citations
“…Based on the composition analysis of milk from the Istrian jennies and the Littoral Dinaric jennies, the values of lactose, protein, fat, and ash content fell within the range of the previously determined values [17,18,[20][21][22][23][25][26][27][28][29][38][39][40][41]. These studies reported lactose content ranging from 5.75 to 7.25%, protein content ranging from 1.42 to 2.04, fat content ranging from 0.11 to 1.16%, and ash content ranging from 0.36 to 0.51% (Figure 2).…”
Section: Donkey Milkmentioning
confidence: 82%
“… Average values of lactose, protein, fat, and ash content in milk from different donkey breeds (according to different authors) [ 17 , 18 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 38 , 39 , 40 , 41 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…This is the first study to isolate DNA from the milk somatic cells isolated from the Halari breed of Indian donkeys. The Halari donkey breed of India is recently registered (Accession No: INDIA_DONKEY_0400_HALARI_05002) and is primarily found in the state of Gujarat, India [ 29 ]. Our results imply (1) the first report of DNA isolation from the milk of Halari donkey as a non-invasive alternate to other invasive or minimally-invasive methods, (2) the first characterization of k-casein gene from isolated DNA from the Halari donkey milk somatic cells.…”
Section: Discussionmentioning
confidence: 99%